2015
DOI: 10.17269/cjph.106.4918
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries disparities in early childhood: A study of kindergarten children in British Columbia

Abstract: OBJECTIVE: The objective of this paper was to describe results of a public health-administered, provincial dental survey of children aged 4-6 years old in British Columbia, and assess the changes in rates of dental caries geographically and by neighbourhood socio-economic status between baseline (2006/07) and follow-up data collection (2009/10). METHOD:The study design involved two retrospective cohorts of kindergarten children who received a public health-administered dental assessment in the years 2006/07 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The education of parents influences the prevalence of ECC of children (41)(42)(43)(44), where the results of our study also confirm that the higher the level of parental education was, the lower the prevalence of early childhood caries. Moreover, it has been suggested that the lower levels of parental education can be associated with a decreased financial ability which contributes to compromised overall access to dental resources, namely, decreased opportunities for dental checkups and dental visits (45).…”
Section: Discussionsupporting
confidence: 83%
“…The education of parents influences the prevalence of ECC of children (41)(42)(43)(44), where the results of our study also confirm that the higher the level of parental education was, the lower the prevalence of early childhood caries. Moreover, it has been suggested that the lower levels of parental education can be associated with a decreased financial ability which contributes to compromised overall access to dental resources, namely, decreased opportunities for dental checkups and dental visits (45).…”
Section: Discussionsupporting
confidence: 83%
“…The advanced form of ECC, known as severe ECC (S-ECC), refers to atypical or progressive or acute or rampant patterns of dental caries (American Dental Association, 2000Association, , 2004. Poon, Holley, Louie, and Springinotic (2015) noted that, "most studies of dental caries in young Canadian children involved smaller, non-representative samples of subpopulations. "…”
Section: Dental Caries In Children (Below 6 Years) In Canadamentioning
confidence: 99%
“…Estimates suggest that 60 to 90% of school-aged children have some form of tooth decay [2] and in Canada, up to half of all children enter kindergarten with tooth decay [3, 4]. While tooth decay is common across the globe [5], it is also a marker for health inequalities, with people of lower socioeconomic status (SES) experiencing poorer oral health [69]. Poverty is related to a higher risk of dental caries, unaddressed dental needs (UDNs), and poor oral health-related quality of life [10].…”
Section: Introductionmentioning
confidence: 99%